The Association Between Ischemic Heart Disease and Hypertension in Libyan Adults: A Cross-Sectional Study - Balha, Ahmed; Fadhlullah, Ali; Razk Abdalgwad (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. It is well known that hypertension is the most important and modifiable risk factor of ischemic heart disease (IHD). We aimed to explore in the current study if there is an association between hypertension and IHD among a cohort of Libyan adults. Methods. A cross-sectional study was conducted on patients who attended to the cardiac clinic at Alwahada Teaching Hospital at Derna city and were diagnosed with IHD and hypertension. We examined the likelihood occurrence of IHD in hypertensive patients using the Bayesian one sample test. Results. In total, 97 patients with IHD were included in this study. The mean age was 60 ± 11.89 years (P = 0.933). 53 (54.6%) were females, while 44 (45.4%) were males; respectively.63 (64.9%) of patients had hypertension as compared to 34 (35.1%) who did not have hypertension. The likelihood of occurrence of IHD in the hypertension group was significantly higher than in the non-hypertension group at percentages of 63 (64.9%), and 34 (35.1%), (P = 0.002), respectively. Conclusion. The current outcomes found that there was a significant relationship between hypertension and IHD and this study highlights the importance to consider the optimal blood pressure control to minimize the possibility of occurrence of IHD in established patients with hypertension.